Non-pharmacological interventions for the prevention of type 2 diabetes in low-income and middle-income countries: a systematic review of randomised controlled trials - K M Saif-Ur-Rahman; Md Shariful Islam; Anupam Sarker; Rina Das; Saraban Ether (BMJ Open)
Objective Diabetes poses serious health threats and economic burdens to patients, especially in low-income and middle-income countries (LMICs). This systematic review searches for non-pharmacological interventions for the prevention of type-2 diabetes mellitus (T2DM) among patients who are non-diabetic and pre-diabetic from LMICs.Settings LMICs.Participants Adult population aged over 18 years without having diabetes.Primary and secondary outcomes Primary outcome is to measure the change in the incidence of T2DM. The secondary outcome is to measure changes in glycated haemoglobin (HbA1c) level, weight/body mass index (BMI), fasting glucose level and 2-hour glucose from baseline of the included randomised controlled trials.Methods This review has been conducted following the standard systematic review guidelines. A total of six electronic databases including MEDLINE, Embase, the Cochrane Library, Web of Science, ClinicalTrials.gov and International Clinical Trials Registry Platform were searched in February 2021 using a comprehensive search strategy.Two sets of independent reviewers performed screening, risk of bias (ROB) assessment using the Cochrane ROB tool and data extraction. Narrative coalescence of selected articles was demonstrated using tables. No meta-analysis was performed due to the lack of homogenous intervention strategies and study settings.Result A total of five studies were included for the review with a combined population of 1734 from three countries. Three of the studies showed a significant reduction in T2DM incidence after the intervention of physical training and dietary modifications. Four of the studies also demonstrated a significant reduction of different secondary outcomes like weight, BMI, fasting and 2-hour plasma glucose and HbA1c. All the studies demonstrated a low ROB in most of the bias assessment domains with some unclear results in allocation concealments.Conclusions Emphasising non-pharmacological interventions for T2DM prevention can improve health outcomes and lessen the economic burdens, which will be of paramount importance in LMICs.Systematic review registration number CRD42020191507